Prevalence of Child Marriage and its Associated Factors - Timalsina, Keshab Prasad; Baral, Rameshor; Budhathoki, Drona; Sanjel, Govinda Prasad; Dhungel, Basu Prasad; Sapkota, Jagganath; Chaulagain, Anju; Timalsina, Bhim Prasad (International Research Journal of MMC, 2023)
The purpose of the research is to study the prevalence of child marriage. Further it aimed to assess the associate factors of child marriage. Since mixed method of data collection and analysis was used in this study, this researched was based on an explanatory sequential research design. Since the study used secondary sources of data, it was based on a census-style survey of the Bhimphedi Rural Municipality that included all marriages (569 cases) that took place within the previous three years of the survey date. This study observed 34.3% prevalence of child marriage in the study area in which prevalence was found high among Buddhist (41.6%) from religion group, female (49.5%) from gender group, basic level of education (80.2%) from level of education group, lower economic class (72.7%) from economic class group, single family (43.1%) from type of family group, arrange marriage (37.2%) from nature of marriage group, and Chepang (52.0%) in cast group. Since the p-values for selected socio-demographic characteristics of married person were < 0.05 except the nature of marriage, this study concludes that prevalence of child marriage is significant with religion, gender, level of education, economic class, and caste/ethnicity of the married people. To avoid the practice of child marriage in Nepal, multi-sectoral actions and policies should be developed and strictly implemented.